PEMETAAN TREN RISET ARTIFICIAL INTELLIGENCE DALAM PENDIDIKAN ISLAM: ANALISIS BIBLIOMETRIK 2018-2025 - Saputra, Amri; Cahyati, Dini (IAI Sunan Giri Trenggalek, 2026)
The integration of Artificial Intelligence (AI) into religious education systems has become an increasingly pressing topic amidst the global digitalization wave. This study aims to map the scientific landscape, growth trends, and conceptual structure of research regarding the application of AI in Islamic Education. Employing a bibliometric analysis approach assisted by the R-package Biblioshiny software, this study analyzed 30 selected documents published between 2018 and 2025. The results indicate that this topic is a rapidly emerging research field, characterized by a high annual growth rate of 51.12%. A significant surge in publications was identified starting in 2023, strongly correlating with the emergence of generative AI technologies. Geographically, Indonesia dominates the global contribution map as the most productive and most cited country, far surpassing other nations. Thematic analysis reveals that current research focus centers on the use of ChatGPT in higher education and the development of intelligent technologies for Quran memorization. This study concludes that although still in its nascent stage, the integration of AI in Islamic education holds immense potential but requires broader international research collaboration.